MAKNA DAN FUNGSI REDUPLIKASI PADA NOVEL REDUP MATAHARI DI MONOKERTO - Simaremare, Juni Agus; Sitorus, Crisdayanti; Pakpahan, Iren Rut Serlina; Wa, Yerni (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The aim of this research is to describe the meaning and function of reduplication in the novel Redup Matahari di Monokerto. The research method we use is qualitative method with data collection techniques and reading techniques. In the results of the study we will find the meaning of reduplication from the novel Redup Matahari di Monokerto such as referring to phenomena, emphasizing the intensity of the statement, emphasizing that an action occurs repeatedly, to express intense curiosity emphasizing giving sudden nuances, to convey the meaning that there are many birds, to show the diversity of variations in facial appearance, to show specialty in choice to show plurality in a group, to show the intensity / continuity of an action / state or to give nuance to the meaning of words, to emphasize the presence of more than one shelf, to express a very high or intense level of admiration, to show intense concern, to refer to various clues or indications, to show the speed of an action or movement, to imply a less clear picture, to show affirmation or emphasis of a negative situation, to show more than one book, to refer to various clues or indications, to show affirmation or emphasis of a negative situation, to show a large number in an action. The function of reduplication from the novel Redup Matahari di Monokerto such as verb formers, adverbial formers, adjective formers, noun formers.